Acupuncture therapy for Alzheimer's disease: A protocol for an overview of systematic reviews. Issue 21 (22nd May 2020) - Wang, Liaoyao; Xu, Jia; Zhan, Yijun; Pei, Jian
Abstract: Background: Alzheimer's disease (AD) is the fifth-leading cause of death in people more than 65 years old. Acupuncture therapy has been traditionally used to treat various kinds of health problems including AD. This protocol aims to summarize the available evidence from current systematic reviews (SRs) for the efficacy of acupuncture therapy for AD. Methods: Seven databases will be searched: PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Wanfang Data, Chongqing VIP (CQVIP), and Chinese Biomedical Literature Database (CBM). SRs/meta-analyses (MAs) of acupuncture therapy for AD which were reported in Chinese or English will be included. Study selection, data extraction, and assessment of the study quality will be performed independently by 2 or more reviewers. And the methodological quality, report quality and evidence quality will be evaluated by Assessment of Multiple Systematic Reviews-2 (AMSTAR-2) tool, Preferred Reporting Items for Systematic Reviews and Meta Analyses Statement (PRISMA) checklist and Grading of Recommendations Assessment, Development and Evaluation (GRADE) system, respectively. Results: The article in this overview will be submitted for publication in a peer-reviewed journal. Conclusion: We expect to compile evidence from multiple systematic reviews of acupuncture therapy in AD patients in an accessible and useful document. Registration number: INPLASY202040035. Abstract : Supplemental Digital Content is available in the text